SPECIFIC ASPECTS OF COLLECTIVE MANAGEMENT ORGANIZATIONS - Iroda Yakubova (Scholar Express Journal, 2022)
Within the framework of the subject, it was studied in detail how right holders enter into agreements with persons using works (objects of copyright and related rights) on their own behalf on the basis of powers granted by collective management organizations, as well as collection, distribution and payment of royalties to right holders. Attention is paid to some urgent problems related to the improvement of this institution, international standards for copyright protection and comparative legal analysis of national legislation, as well as the opinions of scientists from Uzbekistan and other different countries. Suggestions and recommendations were put forward of scientific and practical importance for national copyright law.
Keywords: copyright; to enforce copyright; royalty; copyright and related rights collective management